2022
DOI: 10.7324/japs.2023.130105
|View full text |Cite
|
Sign up to set email alerts
|

Statically improved fungal laccase-mediated biogenesis of silver nanoparticles with antimicrobial applications

Abstract: Green synthesis of silver nanoparticles (AgNPs) using microbial enzymes has gained great attention owing to its advantages, such as cost-effectiveness, biocompatibility, eco-friendliness, and simplicity, over conventional physical and chemical methods. In our study, the laccase enzyme of an unconventional source like the endophytic strain Alternaria arborescens MK629314 was optimized and applied for AgNP biogenesis. Alternaria arborescens laccase enzyme production was first improved using a three-factor, five-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…And then the cells were incubated at 37C o in 5 %CO 2 and 95% humidity. Cells were subcultured using trypsin 0.15 % Alharbi et al, 2020).…”
Section: Cytotoxicity Assay 251 Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…And then the cells were incubated at 37C o in 5 %CO 2 and 95% humidity. Cells were subcultured using trypsin 0.15 % Alharbi et al, 2020).…”
Section: Cytotoxicity Assay 251 Cell Culturementioning
confidence: 99%
“…Most of these synthetic methods are hazardous due to application of toxic chemical agents which pose environmental problems and biological hazards (Mehndiratta et al, 2013). In recent times, much effort is being focused, by researchers, to prepare AgNPs using "green chemistry approaches", in which silver salts are biologically reduced to AgNPs using nontoxic and natural low cost polymers such as bacterial biomass (Abd El Aty and Zohair, 2020), Fungi , algae (Alharbi et al, 2020), Yeasts (Ammar et al, 2021), plant extracts (Parveen et al, 2016) and extracts of different natural gums, i.e., kondagogu-gum (Rastogi et al, 2014), salmalia malabarica gum (Murali krishna et al, 2015) guar gum Mishra 2014, Pandey andMishra, 2016), ghatti gum . These biopolymers are used as both stabilizing and reducing agents (Demchenko et al, 2020;Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that laccase [ 146 , 230 , 231 , 232 ], Mn-peroxidase [ 146 ], tyrosinase [ 146 ] and ligninase [ 231 ] are involved in AuNP biosynthesis by fungi. Nitrate reductase [ 233 ], laccase [ 234 , 235 ] and xylanase [ 48 ] are involved in the AgNP mycosynthesis, while PtNP synthesis is catalyzed by hydrogenase [ 159 , 160 ]. The same culture can produce several enzymes catalyzing nanoparticle fabrication; for example, for P. chrysosporium , laccase and ligninase have been shown to be responsible for the extracellular and intracellular AuNP formation, respectively [ 231 ].…”
Section: Mechanisms Of Fungi-mediated Nanoparticle Biosynthesismentioning
confidence: 99%